Increasing liana abundance and biomass in tropical forests: emerging patterns and putative mechanisms - Schnitzer, Stefan A; Bongers, Frans (Ecology letters, 2011)
Ecology Letters (2011) 14: 397-406 ABSTRACT: Tropical forests are experiencing large-scale structural changes, the most apparent of which may be the increase in liana (woody vine) abundance and biomass. Lianas permeate most lowland tropical forests, where they can have a huge effect on tree diversity, recruitment, growth and survival, which, in turn, can alter tree community composition, carbon storage and carbon, nutrient and water fluxes. Consequently, increasing liana abundance and biomass have potentially profound ramifications for tropical forest composition and functioning. Currently, eight studies support the pattern of increasing liana abundance and biomass in American tropical and subtropical forests, whereas two studies, both from Africa, do not. The putative mechanisms to explain increasing lianas include increasing evapotranspirative demand, increasing forest disturbance and turnover, changes in land use and fragmentation and elevated atmospheric CO₂. Each of these mechanisms probably contributes to the observed patterns of increasing liana abundance and biomass, and the mechanisms are likely to be interrelated and synergistic. To determine whether liana increases are occurring throughout the tropics and to determine the mechanisms responsible for the observed patterns, a widespread network of large-scale, long-term monitoring plots combined with observational and manipulative studies that more directly investigate the putative mechanisms are essential.